Dietary intakes and body composition of Māori and Pacific women in the women's EXPLORE study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Lawn, Alexandra Leita Gail (Massey University, 2017)
The most thorough record of dietary intake among New Zealand (NZ) Māori and Pacific women was undertaken in the 2008 NZ Adult Nutrition Survey, but it did not consider the relationship with body composition. The aim of this study was to investigate the relationship between dietary intake and body composition (particularly body mass index (BMI) and body fat (BF) percentage) of all Māori (n=79) and Pacific (n=75) women (16-45 years old) recruited in the women’s EXPLORE study. Anthropometric data was measured using weight, height, and air displacement plethysmography (BodPod), while dietary data was assessed using a validated, 220-item, semi-quantitative food frequency questionnaire. On average, the BMI (28.2 kg/m2) and BF (34.6%) of Māori women classified them as overweight, while the average BMI (31.9 kg/m2) and BF (37.8%) of Pacific women classified them as obese. There were significant positive correlations between the BMI and BF percentage of Māori (r=0.86) and Pacific women (r=0.87), which suggests BMI is a good indicator of BF percentage in these populations. The percentage of Māori and Pacific women who exceeded their estimated energy requirement was similar and identical to the percentage of women found in the obese BF percentage groups, respectively. Dietary intake was compared with NZ guidelines, revealing that both groups of women consumed inadequate carbohydrate. In contrast, both groups consumed excess total and saturated fat, and sodium in excess of the upper level, mostly due to high intakes of takeaways. Takeaways were also the top contributor of total energy (13.4%), protein (13.4%) and fat (17.7%) in Pacific women. Obese Māori women consumed more takeaways (42.7%) than non-obese. Obese Pacific women consumed more discretionary breads, cereals and starchy foods (e.g. iced buns, croissants and paraoa parai (fry bread)) (210%) than non-obese. Recommendations include reducing takeaways, fats (e.g. butter), and sugar-sweetened beverages. Instead, opt for more complex carbohydrates and leafy green vegetables. Further research should investigate relationships between dietary intake and waist circumference, as well as other factors influencing body composition, such as physical activity and level of deprivation.
Keywords: Women, Maori; Women, Polynesian; Women, Melanesian; Nutrition; Body composition; Nutrition surveys; New Zealand; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Domestic science and nutrition